STUDY OF ASPIRIN EFFECT ON STABILITY OF MEMBRANES OF RAT BLOOD ERYTHROCYTES BY ACIDIC HEMOLYSIS METHOD (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
In this work the effect of aspirin on stability of rat blood erythrocyte membranes was studied, using acidic hemolysis method. Hemolysis rate of erythrocytes was shown to depend on preservation time of rat erythrocyte suspension. With increasing of preservation time the original value of optic density of rat erythrocyte suspension decreases and hemolysis time reduces. It was also shown that in the presence of aspirin the membrane stability of low-stable erythrocytes increases, moreover, hemolysis duration enhances, while aspirin leads to decreasing of membrane stability of both high-stable and enhanced-stable erythrocytes of rats.
Keywords: erythrocyte membrane; acetylsalicylic acid; erythrocyte stability; hemolysis duration